OTORITAS HADIS DI ERA KECERDASAN BUATAN: TELAAH FILOSOFIS ATAS PERAN CHATGPT DALAM PRODUKSI PENGETAHUAN KEISLAMAN - Mohammad Nawir; Muhammad Muammar; Fitriya N.Laiya (Department of Islamic Theology and Philosophy, UIN Datokarama Palu, 2026)
This article examines the transformation of epistemology in hadith studies in the era of artificial intelligence, with a particular focus on ChatGPT as an epistemic mediator. The study employs a qualitative approach through library research and philosophical analysis of sanad, scholarly authority, and digital technology. The findings indicate a shift from a sanad-based epistemology to a system-based epistemology, marked by the emergence of algorithmic authority. ChatGPT does not possess scholarly authority in the traditional sense but functions as a generative, non-sanad, and pseudo-neutral tool. The use of AI in hadith studies raises several philosophical problems, including the crisis of authority, the validity of knowledge, and the legitimacy of scholarship. Nevertheless, AI also offers opportunities to enhance accessibility and Islamic digital literacy. Therefore, this article proposes the concept of a hybrid epistemology as a constructive framework, integrating Islamic scholarly traditions with digital technology. In this model, AI serves as an assistive tool, while epistemic authority remains grounded in scholars, classical texts, and established scientific methodologies.